An Exploration study into Good Governance and Equity Aspects of JKN Program in Cardiovascular Care Services in Central Java, Indonesia - Suryani Yulianti; Edit Oktavia Manuama; Tri Aktariyani; Tiara Marthias; Laksono Trisnantoro (Jurnal Kebijakan Kesehatan Indonesia, 2021)
To achieve equitable access of its citizen to health care, since 2014, the Government of Indonesia has implemented the national health insurance scheme, namely JKN. However, equal access to specialistic health care is still challenging. Using a convergent parallel mixed-method approach, and the utilization of cardiovascular services as an example, this study aims to evaluate the good governance and equity aspects of the JKN program in Central Java, a province in Indonesia which records a high poverty rate above the national rate. Based on IHME, Central Java has the highest proportion of mortality associated with cardiovascular diseases among the provinces in Indonesia. This study found that most of the districts in this province are struggling to achieve the 2019 JKN roadmap target in terms of JKN participation coverage.  Unequal distribution of health facilities and human resources is recorded affecting access to and utilization of cardiovascular care services. More contribution from the district and provincial government as well participation from private sectors (the employers) to fund the JKN program is essential to ensure the availability of specialistic care services in rural areas to narrow the gaps in cardiovascular care services.